O pewnym problemie niestacjonarnych drgań powłok pod wpływem obciążeń przypadkowych - Skalmierski, B.; Czogała, E. (Engineering Transactions, 1969)
The authors considered the problem of nonstationary random vibrations of cylindrical thin-walled closed shells. The elastic and internal damping characteristics of the shell material are assumed to be linear. The correlation method has been employed and the moments are determined with the exactness to the moments of the second order of displacements. The paper is illustrated with examples in which the displacements variances has been numerically computed as functions of coordinates and time.